Economic potential of AVIKASIL-S technology for estrus synchronization in sheep - NIKAM, VINAYAK; KUMAR, SHIV; KINGSLY, I T; BALAJI, S J; JHAJHRIA, ABIMANYU; KUMAR, RAJ; KUMAR, DAVENDRA (The Indian Journal of Animal Sciences, 2020)
The study captures the economic benefits of AVIKASIL-S, an estrus synchronization technology in sheep using an economic surplus approach in the Rajasthan state of India. The adoption of technology at the field level was at a nascent stage. Study simulated scenarios at different adoption rates of technology and discerned that technology has the economic power to enhance the income of shepherds in the state. To reap the more benefits of technology, the adoption rate needs to increase. The support of government, private sector, and public-private partnership models besides entrepreneurs are the channels for wider adoption of technology amongst shepherds.